Improving the Competence of Writing Scientific Papers for Family Planning Field Workers Through the Reverse Writing Method and Socio Emotional Franchising - Sekarpuri, Anindita Dyah; Rubini, Bibin; Hardhienata, Soewarto (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The aim of this research is to find a writing training pattern that makes it easier for Indonesian Family Planning Field Workers and raises motivation to write, which can have an impact on the lack of results in the form of writing from Family Planning Field Workers. This research uses a mix method with research and development, namely the ADDIE method. Researchers developed online training using “writing with the reverse method” for Indonesian family planning field workers and became a solution for initiative during activities and post pandemic COVID-19 by establishing good collaboration with the population and family planning training center. The output of the innovation is in the form of three printed books, a Copyright certificate for the book Population Education and Family Planning, training tools in the form of the scientific writing training curriculum, training modules, teaching materials, broadcast materials and also learning designs as well as a Memorandum of Understanding between the training and publishing partners and private training providers. The conclusion of this research is that there is an increase in the writing skills of family planning instructors by 87% with the output in the form of participants’ written works. With the concept of mutual benefit and inclusion, it is hoped that this networking activity in improving family planning field workers writing competency will be a means for Indonesian family planning and population Board employees to grow together. It is recommended that this activity be sustainable and have more leverage in the future.